Does robotic assisted technology improve the accuracy of acetabular component positioning in patients with DDH?. (22nd July 2021) - Zhou, Yixin; Shao, Hongyi; Huang, Yong; Deng, Wang; Yang, Dejin; Bian, Tao
Background: Accurate positioning of the acetabular component is key in performing total hip arthroplasty (THA). However, reconstruction of the acetabulum in the setting of developmental dysplasia of the hip (DDH) is a challenge. Robotic assisted THA has the potential to improve the accuracy of implantation of the acetabular cup in cases with DDH. The purpose of this study was to assess whether robotic technology improves the accuracy of acetabular component positioning in patients with DDH. Material and methods: We included 59 THAs using robotic assisted technology from June 2019 to January 2020 as the study group. These were compared to conventional THAs without robotic technology after control for age, gender, body mass index (BMI), Crowe type and operation date. Radiographic measurements were taken by 2 blinded orthopaedic residents. The percentage of hips within the Lewinnek and Collanan safe zones were calculated, along with acetabular rotation centers for the "target zone." Surgical time and perioperative bleeding were also compared between both groups. Results: One patient suffered dislocation in conventional group while no dislocation occurred in robotic group. The acetabular components of the robotic assisted group had more cases located within the Lewinnek ( p = 0.013) and Collanan ( p = 0.008) safe zones than conventional group (94.9% vs 79.7% and 74.6% vs 50.8%). There were 7 cases in conventional group and 4 cases in robotic group that had more lateral or more superior rotational centers of THA, but did not reach statistical significance ( p = 0.342). No statistical difference was detected between groups with regards to blood loss ( p = 0.098) and surgical time ( p = 0.602). Conclusion: Robot assisted technology can assist surgeons with implanting acetabular cups more in Lewinnek and Callanan safe zone than conventional techniques without additional blood loss and surgical time. Level of Evidence: Therapeutic Level Ⅲ.